Wireless public safety networks : Vol. 1 : Overview and challenges - e uthor; Nikaein, Navid (Amsterdam : Elsevier, 2015)
Wireless Public Safety Networks, Volume One: Overview and Challenges presents the latest advances in the wireless Public Safety Networks (PSNs) field, the networks established by authorities to either prepare the population for an eminent catastrophe, or as support during crisis and normalization phases. Maintaining communication capabilities in a disaster scenario is crucial for avoiding loss of lives and damages to property. Wireless Public Safety Networks examines past communication failures that have directly contributed to the loss of lives. This book will give readers a broad view of the PSNs field, analyzing the benefits PSNs may bring to society, the main challenges related to the establishment and maintenance of these networks, the latest advancements in the field, and future perspectives.
2.4. Public Safety Communication Requirements and Main Challenges 2.5. Conclusions ; 2.6. Bibliography ; Chapter 3: Next-Generation Communication Systems for PPDR: The SALUS Perspective.
1. Introduction to Public safety networks>2. Communication technologies>3. Existent and future architectures>4. Requirements for PSN interoperability>5. Emergency alert systems>6. Public Safety Scenarios modelling>7. Fast deployable networks>8. Public Safety applications>9. Validation of mission critical networks protocols>10. Emerging standards>11. Spectrum policies and specific legislations>12. Social networks and disaster scenarios>13. Next generation systems>14. Next challenges.
CIP data; item not viewed.
Keywords: Public safety -- Technological innovations; Wireless communication systems; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Wireless communication systems; Electronic books